2020
DOI: 10.3390/jcm9030732
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition, Serum Concentrations of Androgens and Insulin Resistance in Different Polycystic Ovary Syndrome Phenotypes

Abstract: Insulin resistance and hyperandrogenemia observed in polycystic ovary syndrome (PCOS) are associated with metabolic disturbances and could be connected with body composition pattern. To date, several studies defining the parameters of body composition using dual energy X-ray absorptiometry (DXA) method in the group of PCOS patients have been published, however, without the analysis in different phenotypes. The aim of the present study was to investigate the relationships between serum androgens concentration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 32 publications
1
28
3
1
Order By: Relevance
“…However, in contrast with our results, they did not find a statistically significant difference between phenotype D vs phenotype B and C [31]. Polak's study showed that the mean of FAI in hyperandrogenic phenotypes of PCOS was markedly higher than control group while phenotype D and control groups were similar [32]. In the comparison of PCOS subgroups in terms of FAI, there was a significant increase only in phenotype A compared to the phenotype D [32].…”
Section: Discussioncontrasting
confidence: 99%
“…However, in contrast with our results, they did not find a statistically significant difference between phenotype D vs phenotype B and C [31]. Polak's study showed that the mean of FAI in hyperandrogenic phenotypes of PCOS was markedly higher than control group while phenotype D and control groups were similar [32]. In the comparison of PCOS subgroups in terms of FAI, there was a significant increase only in phenotype A compared to the phenotype D [32].…”
Section: Discussioncontrasting
confidence: 99%
“…By showing a similar effect of androgen excess in the group with one Rotterdam criterion only (1RC), we were able to show that metabolic changes not only occur in women with two or more PCOS criteria, but also in women with hyperandrogenemia alone. Some previous studies have described a similar effect with regard to risk of diabetes or the metabolic syndrome [ 7 , 31 ]. However, they did not assess the early effect of developing IR, nor did they take into account the potential PCOS phenotypes using the Rotterdam criteria.…”
Section: Discussionmentioning
confidence: 55%
“…In our cohort, phenotypes with HA (A-C) had higher average values of BMI and HOMA, while showing lower SHBG and Matsuda values. Previous studies by Polak et al and Gupta et al did not find any significant differences in IR prevalence [ 7 , 28 ]. However, this could be explained by a lower sample size (146 and 150, respectively, compared to 750 women included in our analysis) and their lack of Matsuda index calculation.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Clinically, it is characterized by persistent non-ovulation, bio-chemical or clinical manifestations of high androgens, and ovarian polycystic changes, and it often accompanied by obesity and insulin resistance. [ 3 4 ] At present, the pathogenesis of PCOS is not completely clear, some studies believe that genetic factors, the abnormalities of hypothyroidism-pituitary-ovary axis regulation, adrenal endocrine mechanism disorders, ovarian local side secretion and self-secretion regulation mechanism imbalance, hypersotrophicemia and insulin resistance, the imbalance between inflammation factors and anti-inflammatory factors may lead to the occurrence of the disease. [ 5 6 ]…”
Section: Introductionmentioning
confidence: 99%